Pengaruh Pendidikan Karakter dan Lingkungan Sosial terhadap Persepsi Sikap Etis Pada Mata Kuliah Etika Bisnis dan Profesi - Clearesta Ulima Aspasia; Marsofiyati Marsofiyati (Journal Innovation In Education, 2024)
This study aims to analyze the impact of character education and social environment on students' ethical attitudes in the Business Ethics and Professional Ethics course within the Office Administration Education Program. The research employs a survey method, collecting data through questionnaires distributed to 36 students. Data analysis reveals that both character education and social environment significantly influence students' ethical attitudes. The integration of character education into the curriculum plays a crucial role in fostering ethical awareness, while a positive social environment reinforces ethical values. This study recommends the need for synergy between educational programs emphasizing ethics and supportive social environments to prepare students for ethical challenges in their careers. The findings are expected to contribute to the development of more effective curricula and educational policies aimed at instilling ethical attitudes among students.